2020
DOI: 10.34179/revisem.v5i2.12654
|View full text |Cite
|
Sign up to set email alerts
|

Formação continuada de professores de matemática: um olhar para as metodologias ativas nos processos de ensino e de aprendizagem

Abstract: O objetivo deste artigo é apresentar os desdobramentos que um curso de formação continuada, oferecido pelo Centro de Referência em Tecnologia Educacional, proporcionou a um grupo de professores de Matemática, para a utilização das tecnologias digitais enquanto uma metodologia ativa. Salientamos que o Centro de Referência em Tecnologia Educacional pode ser equiparado aos Núcleos de Tecnologia Educacional dos demais estados brasileiros e uma das características deste centro é a oferta de cursos e oficinas que es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The horizontal analysis of this section followed the classification of "focus of analysis" because we could investigate whether the objectives had been achieved and what the implications were. In the first group-using dynamic geometry software-we identified that research (Chinellato & Javaroni, 2020;Nogueira et al, 2020;Zambak & Tyminski, 2020) recognize the potential of dynamic geometry software for mathematics classes. The articles highlight that the interaction between the physical and digital environment benefits teachers' development.…”
Section: Results Conclusion and Implicationsmentioning
confidence: 99%
“…The horizontal analysis of this section followed the classification of "focus of analysis" because we could investigate whether the objectives had been achieved and what the implications were. In the first group-using dynamic geometry software-we identified that research (Chinellato & Javaroni, 2020;Nogueira et al, 2020;Zambak & Tyminski, 2020) recognize the potential of dynamic geometry software for mathematics classes. The articles highlight that the interaction between the physical and digital environment benefits teachers' development.…”
Section: Results Conclusion and Implicationsmentioning
confidence: 99%